Peran Public Relations dalam Membangun Citra Positif dan Kepercayaan Melalui Program Tanggung Jawab Sosial dan Lingkungan PT Pupuk Iskandar Muda - Saifuddin, Saifuddin (Mahesa Research Center, 2025)
This study aims to explain the role and obstacles of public relations in building a positive image and increasing the trust of the fostered village community through the Social and Environmental Responsibility (TJSL) program. This study uses a qualitative approach with interviews, observations, and documentation involving informants from the company, fostered village communities, village heads, community leaders, Muspika Dewantara District, and the mass media. The results of the study indicate that the role of PT PIM's public relations is to communicate the company's program for the development and welfare of the fostered village community, be responsible for conveying every information on the TJSL assistance program, manage public opinion and establish communication with the media and stakeholders, manage and promote the TJSL assistance program with positive contributions, and conduct an Environmental Satisfaction Survey to assess the community's response to its performance. The results of the study also explain the obstacles to public relations, namely PIM's financial and human resource limitations, community expectations are too high for TJSL assistance, expected grant assistance (charity), the community's education level being relatively low, and there is still a lack of community trust in PIM.